PENERAPAN LINGKUNGAN BAHASA ARAB DALAM MEMBANGUN KEPERCAYAAN DIRI SANTRIWATI DI PM DAARUL UKHUWWAH MALANG - Jumahir, Al Magfira; Abidin, Munirul; Yurisa, Penny Respati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Arabic language environment (bi’ah lughawiyyah) in building the self-confidence of female students at Daarul Ukhuwwah Islamic Boarding School, Malang. This research employs a qualitative approach with a descriptive method, as it seeks to provide an in-depth description of how the Arabic language environment is implemented in a modern Islamic boarding school. Data were collected through observation, interviews, and documentation. The data analysis techniques included data reduction, data display, and conclusion drawing. The findings indicate that the implementation of bi’ah lughawiyyah is carried out systematically through mandatory language policies, daily communication habituation, and structured programs such as muhadatsah, muhadharah, and other language activities integrated into the daily life of the boarding school. This language environment functions not only as a means of improving linguistic competence but also as a medium for developing affective aspects, particularly students’ self-confidence. This is evidenced by increased speaking courage, the ability to express ideas, and a reduction in language anxiety. However, the effectiveness of the language environment is influenced by internal factors such as students’ linguistic backgrounds and psychological conditions, as well as external factors such as institutional support and peer social dynamics. Therefore, the success of bi’ah lughawiyyah is determined not only by the intensity of language use but also by the quality of a supportive and adaptive environment in managing students’ psychological aspects. Keywords: Bi’ah Lughawiyyah, self-confidence, Arabic language, Islamic boarding school.